Effects of green supply chain management practices on sustainability performance - Cankaya, Sibel Yildiz; Sezen, Bülent (Emerald Group Publishing Ltd, 2019)
Purpose The purpose of this paper is to explore the impact of eight dimensions of green supply chain management (GSCM) on economic, environmental and social performance, which are the three dimensions of corporate sustainability. The eight dimensions covered in this study are: green purchasing, green manufacturing, green distribution, green packaging, green marketing, environmental education, internal environmental management and investment recovery. Design/methodology/approach The relationships between dimensions of GSCM and sustainability performance are tested by using a plant-level survey. A proposed research model and hypotheses are tested by using cross-sectional face-to-face and e-mail survey data collected from manufacturing firms in Turkey. Structural equation modeling is used to test the proposed hypotheses. Findings Except for green purchasing, all GSCM dimensions are found to be related with at least one of the performance dimensions. Practical implications The results are important in highlighting the importance of GSCM in improving sustainability performance. Originality/value This paper enhances the understanding of the relationship between different dimensions of GSCM and the three sustainability performance factors. While there are very few studies examining the relationship between GSCM and corporate sustainability, this study is important in terms of exploring the effects of dimensions of GSCM applications on economic, environmental and social performance one by one, by examining these applications in the form of eight dimensions.
Keywords: Green manufacturing; Sustainable production; Supply chain management